Stress Testing in Sub-Saharan Africa : Practices, Communications, and Capacity Development - Leika, Mindaugas (Departmental Papers; Departmental Paper ;, 2020)
The paper finds that supervisory stress tests are conducted in more than half of sub-Saharan African countries, particularly in western and southern Africa, and that the number of individual stress tests has grown exponentially since the early 2010s. By contrast, few central banks publish assessments of macro-financial linkages; the focus leans more toward discussing trends and weaknesses within the financial sector than on outside risks that may negatively affect its performance.